2023
DOI: 10.1177/00910260221147692
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Participative Leadership on the Voice Behavior of Public Servants

Abstract: Determining how to stimulate public employees’ voice behaviors has become a critical issue in both theory and practice. This article draws on the theories of participative management, leadership, role theory, and social identity theory and proposes a moderated mediation model to explore the mechanism by which participative leadership shapes public employees’ voice behaviors. To test this study’s hypotheses, we conduct a three-wave investigation of 739 public tax agency employees in the Yangtze River Delta area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 112 publications
1
4
0
Order By: Relevance
“…It could be expected that employees in high-power distance cultures may be less inclined to express their opinions or engage in participative processes, because of the hierarchical structures where they work ( Hofstede and Hofstede, 1991 ). However, this study aligns with previous research that, even in high power distance cultures, there can be a preference for more participatory leadership when given the opportunity ( Robert et al, 2000 ), and that employees’ justice perceptions at work can be facilitated by participative forms of leadership, as has been noticed in several studies previously conducted in high power distance cultures ( Somech, 2006 ; Parnell, 2010 ; Gupta and Singh, 2015 ; Qing and JinHua, 2023 ). Thus, these studies suggest that leadership styles are not solely determined by cultural norms but can also be influenced by how leaders treat their team members.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It could be expected that employees in high-power distance cultures may be less inclined to express their opinions or engage in participative processes, because of the hierarchical structures where they work ( Hofstede and Hofstede, 1991 ). However, this study aligns with previous research that, even in high power distance cultures, there can be a preference for more participatory leadership when given the opportunity ( Robert et al, 2000 ), and that employees’ justice perceptions at work can be facilitated by participative forms of leadership, as has been noticed in several studies previously conducted in high power distance cultures ( Somech, 2006 ; Parnell, 2010 ; Gupta and Singh, 2015 ; Qing and JinHua, 2023 ). Thus, these studies suggest that leadership styles are not solely determined by cultural norms but can also be influenced by how leaders treat their team members.…”
Section: Discussionsupporting
confidence: 91%
“…It has been suggested that participative forms of leadership influence employees’ justice perceptions by fostering open communication with their subordinates ( Larson et al, 1998 ; Somech, 2005 ). By enabling employees to voice their concerns and seek explanations regarding their supervisors’ actions and decisions ( Wang et al, 2022 ; Qing and JinHua, 2023 ), and providing adequate justifications or explanations to employees’ concerns, leaders create the conditions for the emergence of positive justice perceptions among employees ( Shaw et al, 2003 ). Additionally, empirical evidence supports that, when employees perceive they are treated with fairness and respect at work, team learning related dynamics and outcomes emerge ( Dayan et al, 2009 ; Akgün et al, 2010 ; Gerlach, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adopted time lags of one-month intervals as suggested by previous studies (e.g. Ali et al, 2023;Cheng et al, 2019;Holtz and Hu, 2017;Qing and JinHua, 2023;Yao et al, 2020;Zheng et al, 2022) since a one-month time lag was sufficiently long enough to avoid participants' memory effects but not so long that contaminating factors and respondent attrition became a problem. Finally, response biases related to social desirability, demand characteristics and ambiguity in the measurement items were controlled for by improving the scale items.…”
Section: Common Methods Biasesmentioning
confidence: 99%
“…Positive styles of leadership, such as participative leadership [17], moral leadership [18,19], and servant leadership [13,20], have been shown to have a positive in uence on employees' voice behavior. Affective leadership falls into this category, prioritizing the interpersonal relationship between superiors and subordinates over the authority of leaders [15].…”
Section: Hypothesismentioning
confidence: 99%